Current advances and potential trends of the polysaccharides derived from medicinal mushrooms sanghuang - Wang, Hao; Ma, Jin-Xin; Zhou, Miao; Si, Jing; Cui, Bao-Kai (Frontiers in Microbiology, 2022)
Sanghuang is distinctive as a general designation for a group of precious and rare Chinese medicinal mushrooms for thousands of years. Numerous investigations have revealed that polysaccharide is one of the important biological active ingredients of sanghuang with various excellent biological activities, including antioxidant, anti-aging, anti-tumor, immunomodulatory, anti-inflammatory, anti-diabetic, hepatoprotective, and anti-microbial functionalities. For recent two decades, preparation, structural characterization, and reliable bioactivities of the polysaccharides from fruiting bodies, cultured mycelia, and fermentation broth of sanghuang have been arousing extensive interest and particularly, different strains, sources, and isolation protocols might result in obvious discrepancies in structural features and bioactivities. Therefore, this review summarizes the recent reports on preparation strategies, structural features, bioactivities, and structure-activity relationships of sanghuang polysaccharides, which will enrich the knowledge on values of natural sanghuang polysaccharides and support their further development and utilization as therapeutic agents, vaccines, and functional foods in tonic and clinical treatment.